Low frequency hybrid instability in quantum magneto semiconductor plasmas. (1st April 2016) - Rasheed, A; Jamil, M; Areeb, F; Siddique, M; Salimullah, M
Abstract: The excitation of electrostatic, comparatively low frequency, lower-hybrid waves (LHWs) induced by electron beam in semiconductor plasma is examined using a quantum hydrodynamic model. Various quantum effects are taken into account including the recoil effect, Fermi degenerate pressure, and exchange-correlation potential. The effects of different parameters like the electron-to-hole number density ratio, scaled electron beam temperature and streaming speed, propagation angle and cyclotron frequency over the growth, and phase speed of LHWs are investigated. It is noticed that an increase in the electron number density and streaming speed enhance the instability. Similar effects are observed on decreasing the propagation angle with magnetic field.